Empirical Evidence of Television Advertising Effectiveness on Selected Brands of Cellular Phones - Das, Saumendra; Kumar, Kusumuru Vijaya (Journal of Management and Science, 2013)
Every day we are watching enumerable advertisements in different media whether in television or newspaper. Watching advertisements became the part of our lifestyle to select any categories of product or any type of brand. In this regard advertisements played a vital role to inform, persuade and remind us on a product. The types of advertisements in different media with specific location are attracting us to select a particular brand. Thus advertising is not only giving us the information but also pulling us to purchase the products.Almost each and every brand of products are associated with advertisements whether a consumer durable or non durable products. It depends on the market capabilities and also with customer demand. Basing on the demand, the company use to select the market as well creates the need and expectation of consumers. Today cellular phone marketing has become the bandwagon of popular media of reaching the target audience. The cellular phone subscribers in the developed world has already reached saturation point with at least one cell phone subscription per person. All these progress is due to the advertising effectiveness in different media which reveals the growth of telecom sector as well as the penetration of brand. In this article the researcher tried to emphasise the effectiveness of television advertising with a particular brand of cell phone subscription and presented it in an empirical manner by the help of tables.